ANALISIS KESESUAIAN POLA RUANG DENGAN POTENSI PENGEMBANGAN WILAYAH DI KABUPATEN MEMPAWAH - Ayu Anggraini Tambunan; Linus Tabuni; Feby Anazmi (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the suitability of spatial patterns with the potential for regional development in Mempawah District, focusing on the agricultural sector, infrastructure, and socio-economic aspects. The research employs a descriptive analytical approach with a quantitative method. Based on the analysis through various techniques such as spatial analysis and field observations, it was found that the majority of Mempawah’s areas hold great potential for agriculture. However, many areas have experienced land use changes into residential and industrial zones. This has created discrepancies between spatial planning and existing land utilization. The improvement of infrastructure, particularly transportation and utilities, is crucial to support the efficient development of industrial and residential areas. This study provides recommendations for revising spatial plans to be more flexible and able to accommodate the changing spatial needs, as well as enhancing monitoring of land use changes to ensure sustainable development